Enhancing HIV/AIDS knowledge and preventive behaviors among female sex workers: A community-based intervention in Makassar City - Azwar, Muhammad; Syamsul Bahri,; Lilis Widiastuty,; Munadhir, Munadhir (Sociality: Journal of Public Health Service, 2025)
Despite extensive global efforts, HIV/AIDS continues to pose a significant public health challenge in Indonesia, particularly among high-risk populations such as female sex workers. Previous studies have highlighted persistent gaps in HIV/AIDS knowledge and inadequate preventive practices within this community. This study aimed to enhance knowledge and preventive behaviors regarding HIV/AIDS among female sex workers in Makassar City through a structured, community-based intervention. Conducted in May 2025 in Panakukang District, the intervention employed participatory health education methods, including interactive counseling, focus group discussions, and condom-use simulations. A pre- and post-test design was used to evaluate changes in knowledge and behavior. Findings demonstrated a substantial improvement in knowledge scores, increasing from a mean of 54.2 to 85.7. Furthermore, the rate of consistent condom use rose from 62% to 87% following the intervention. The results underscore the effectiveness of community-based, interactive educational approaches in promoting HIV/AIDS prevention. These findings have significant implications for public health strategies targeting similar high-risk urban populations.